Information needs and information seeking behaviors of Social Science graduate students in Malaysian public universities / Ramnah Abd. Thani - Abd. Thani, Ramnah (2009)
The focus of the study was the graduates of Social Science by research to pursue Master and Doctor of Philosophy (Phd) degrees in Public Malaysia Universities. It is believed that the graduates of Social Science by research were in need for large volumes of current and relevant information. However, computerization has changed the graduates' information requirements and seeking behaviors. Thus, this study is to gain a clearer picture on how Social Science graduate students seek for information. It also looks closely at the types of information sources gathered, how and why the information sources were selected. This study also attempts to investigate the barriers faced by the graduates. Additionally, information needs, information skills, individual characteristics, and information seeking strategies are also highlighted which include information tools, modes of communications and the characteristics of information. Extensive reviews of related and relevant literature that include previous and present studies were heavily referred. The sample of the study was the Social Science graduate students of four Local Universities: UiTM, UM, UKM and USM. Quantitative data was collected using close-ended questionnaires and qualitative data was through face-toface and telephone interviews. The statistical package for the Social Sciences (SPSS) version 12 was used to analyze quantitative data and the qualitative data was analyzed separately. Important comments or suggestions were collected from both data. The study concludes that the actual information needs of Social Science graduate students are factors that motivated and urged them to seek for information besides, information seeking behaviors, information skills, availability of information sources, strategies used such as information tools, modes of communication performed, and information characteristics.